2022
DOI: 10.3389/fpls.2022.974507
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose alleviates salt tolerance by improving photosynthetic performance and maintaining mineral ion homeostasis in tomato plants

Abstract: Trehalose (Tre), which was an osmoprotective or stabilizing molecule, played a protective role against different abiotic stresses in plants and showed remarkable perspectives in salt stress. In this study, the potential role of Tre in improving the resistance to salt stress in tomato plants was investigated. Tomato plants (Micro Tom) were treated with Hoagland nutrient solution (CK), 10 mM Tre (T), 150 mM sodium chloride (NaCl, S), and 10 mM Tre+150 mM NaCl (S+T) for 5 days. Our results showed that foliar appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…Key enzymes of the Calvin cycle (RuBisCO, GAPDH, FBA, FBPase, and TK) play an irreplaceable role in photosynthesis 44,45 . RuBisCO and FBPase play important roles in carbon xation: reduction and RuBP regeneration, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Key enzymes of the Calvin cycle (RuBisCO, GAPDH, FBA, FBPase, and TK) play an irreplaceable role in photosynthesis 44,45 . RuBisCO and FBPase play important roles in carbon xation: reduction and RuBP regeneration, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The second leaf of ve plants was selected for a replicate of each treatment. The conditions set during measurement were as follows: leaf area, 1.7 cm 2 ; chamber ow rate, 200 mL min − 1 ; photosynthetically active irradiation, 1000 µmol m − 2 s − 1 ; carbon dioxide (CO 2 ) concentration, 400 µmol mol − 1 ; air temperature, 25℃; and relative humidity, 75% 44 .…”
Section: Measurement Of Photosynthetic Pigments Photosynthetic and Ga...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivated tomatoes had gradually lost their capacity to adapt to high salt stress during the domestication process ( Sato et al., 2012 ). At present, preliminary studies on mechanisms of salt tolerance in tomato had been reported ( Yang et al., 2022 ), but the hormone-related regulatory network of tomato plants under salt stress remained unclear. Further studies on the regulatory networks of hormone metabolism and signal transduction might be important to precisely elucidate the salt stress mechanism of tomato plants.…”
Section: Introductionmentioning
confidence: 99%
“…This crop is extremely vulnerable to abiotic stress brought on by drought, excessive salinity, and extreme temperatures, which can result in yield reductions of up to 15% and an estimated loss of 16 million tonnes of grain [24]. It is therefore necessary to put strategies in place to reduce these losses as [25] who proved that the exogenously application of soaking rice seeds with 25 mM of trehalose could alleviate the harmful effects of salinity stress [26] proved that foliar application of trehalose had significant and positive effect on most growth parameters of wheat plants [27] confirmed that trehalose can efectively alleviate salt stress and enhance salt tolerance of tomato [28] concluded that trehalose treatments (100 µM or 500 µM) had pronounce effect in alleviating the harmful effect of moderate and severe drought stress on cowpea plant and enhanced its drought tolerance [29] demonstrated that trehalose was involved in the process of mitigating salt stress toxicity in tomato plants and provided specific insights into the effectiveness of trehalose in mediating salt tolerance.…”
Section: Introductionmentioning
confidence: 99%